Patients with varying courses of single coronary artery: case series. Issue 10 (3rd September 2021) - Sheng, Calvin C; Ghobrial, Joanna; Cho, Leslie
Abstract: Background: Single coronary artery (SCA) is a rare congenital anomaly where blood to the heart is supplied through a common trunk. Identifying these abnormalities is important because some variants can compromise myocardial blood flow and increase risk of sudden cardiac death. Case summary: We present five patients with varying Lipton Group I and Group II SCA subtypes, corroborated on multi-imaging modalities and evaluated with comprehensive non-invasive as well as invasive testing. Their clinical presentations also vary from a spectrum of asymptomatic finding to angina equivalent. The decision for definitive surgical intervention involving unroofing of the involved vessel depends largely on symptoms and evidence of myocardial ischaemia. Discussion: While SCA findings are often incidental and benign, understanding the origin, branching pattern, and course of the anomalous artery has implications in prognosis and treatment. This usually involves a combination of anatomic assessment with imaging such as coronary Computed Tomography Angiography (CTA), Magnetic Resonance Angiography (MRA), and/or coronary angiography as well as functional assessment with invasive testing using tools like instantaneous wave-free ratio and intravascular ultrasound both at rest and with stress. Individualized treatment plans can then be made through a multidisciplinary approach involving adult congenital heart disease specialists and congenital cardiothoracic surgeons.